Pouring sealant with high thermal conductivity and preparation method thereof
The highly thermally conductive potting glue prepared through composite use of modified bisphenol A type epoxy resin and vinyl silicone oil to solve the problem of sharp rise in working temperature caused by insufficient heat production of electronic components, and realizes a potting glue with high thermal conductivity and high flame retardant performance, improving the stability and reliability of electronic components.
Patent Information
- Application Number
- CN202510062466.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-28
AI Technical Summary
During use, the operating temperature of electronic components increases sharply due to insufficient heat production and effective conduction, which threatens stability and reliability, and shortens the service life of the equipment.
A high thermal conductivity potting adhesive composed of modified bisphenol A-type epoxy resin, polyether polyol, isocyanate ethyl acrylate, silicone coupling agent, etc., and component B-components composed of vinyl silicone oil, dimethyl silicone oil, modified thermal conductivity fillers, etc. is synergistically improved the thermal conductivity of the overall potting adhesive through two forms of thermal conductivity systems.
Potted adhesives with high thermal conductivity and high flame retardant properties can effectively reduce the working temperature of electronic components, improve their stability and reliability, and extend the service life of the equipment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of potting glue preparation, and specifically relates to a high thermal conductivity potting glue and a preparation method thereof. Background Art
[0002] In recent years, microelectronic integration technology has developed rapidly, and electronic components and instruments are also more widely used in the electronics industry. In order to better ensure the stability and reliability of electronic devices, it is often necessary to perform potting and protection treatment on electronic devices. Potting glue is a packaging material used for electronic components. Its main purpose is to protect electronic components from external environmental factors (such as moisture, dust, chemicals and mechanical shock). Potting glue can be filled in the outer shell of electronic products to completely wrap the circuit board or components, providing good insulation and protection.
[0003] There are many types of potting glue, depending on the application and performance requirements. Common ones include: Epoxy resin potting glue: has excellent electrical and physical properties, good heat resistance, high hardness, and is suitable for potting most electronic products. Polyurethane potting glue: has good elasticity, can absorb vibration, and is suitable for occasions that require a certain degree of flexibility. Silicone potting glue: has excellent heat resistance and electrical insulation properties, is resistant to ultraviolet rays, ozone, water vapor, etc., and is suitable for electronic products used outdoors. Acrylic potting glue: has a fast curing speed and high transparency, and is mainly used for products that require rapid processing.
[0004] The development of logic circuits and electronic components is becoming increasingly miniaturized and dense, which will cause a rapid increase in the heat generated per unit area of electronic products. If this heat is not effectively conducted in a timely manner, it will cause a sharp rise in the operating temperature of the circuit, seriously threatening the stability and reliability of electronic devices, and even shortening the life of electronic equipment. Therefore, the development of a high thermal conductivity potting glue has practical significance for the development of electronic components. Summary of the invention
[0005] The purpose of the present invention is to provide a high thermal conductivity potting adhesive and a preparation method thereof, which is compounded by a component A consisting of modified bisphenol A epoxy resin, polyether polyol, ethyl isocyanate acrylate, a siloxane coupling agent, etc. and a component B consisting of vinyl silicone oil, dimethyl silicone oil, a modified thermal conductive filler, allyl glycidyl ether, etc., to obtain a potting adhesive with high thermal conductivity, high flame retardancy and the like.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: A high thermal conductive potting glue is composed of 30-60 parts of component A and 40-70 parts of component B in parts by weight; wherein the component A comprises 40-60 parts of modified bisphenol A epoxy resin, 12-20 parts of polyether polyol, 2-4 parts of isocyanate ethyl acrylate, 1-3 parts of siloxane coupling agent, 0.4-0.8 parts of platinum catalyst, 4-7 parts of hollow glass microspheres and 0.5-1.5 parts of zinc borate; and the component B comprises 30-50 parts of vinyl silicone oil, 8-12 parts of dimethyl silicone oil, 8-12 parts of modified thermal conductive filler, 10-20 parts of allyl glycidyl ether and 1-3 parts of silane coupling agent.
[0007] Furthermore, the epoxy value of the modified bisphenol A epoxy resin is 0.42-0.47 mol / 100g.
[0008] Furthermore, the polyether polyol has a difunctional molecular weight of 2000; the siloxane coupling agent is KH570; and the platinum catalyst is a Karstedt catalyst.
[0009] Furthermore, the modified thermal conductive filler is a mixture of di-spherical alumina, aluminum hydroxide, silicon carbide and modified graphene, and the particle sizes are 2-5 μm, 8-12 μm, and 18-22 μm, respectively.
[0010] A method for preparing a high thermal conductivity potting glue comprises the following steps: S1: by weight, 40-60 parts of modified bisphenol A epoxy resin, 1-3 parts of siloxane coupling agent, 4-7 parts of hollow glass microspheres and 0.5-1.5 parts of zinc borate are mixed, and stirred at a temperature of 120-140° C. for 35-55 minutes; S2: Add 12-20 parts of polyether polyol, 2-4 parts of ethyl isocyanate acrylate and 0.4-0.8 parts of platinum catalyst to step S1 by weight, increase the temperature to 160-180°C at a rate of 4-6°C / min, continue stirring and reacting for 1-3h to obtain component A; S3: Take 3-5 parts of spherical alumina, 4-8 parts of aluminum hydroxide, and 5-10 parts of silicon carbide by weight, wherein the particle sizes of the three are 2-5 μm, 8-12 μm, and 18-22 μm, respectively; add 3-6 parts of graphene and 40-60 parts of ethanol solution, stir and react at a temperature of 80-100°C for 55-75 minutes, and filter to obtain a modified thermal conductive filler; S4: Mix 30-50 parts of vinyl silicone oil, 8-12 parts of dimethyl silicone oil, 8-12 parts of modified thermal conductive filler, 10-20 parts of allyl glycidyl ether and 1-3 parts of silane coupling agent by weight, and react at a temperature of 75-95°C for 35-45 minutes; continue to heat to 140-160°C and stir to react for 55-65 minutes to obtain component B; S5: By weight, 30-60 parts of component A obtained in step S2 and 40-70 parts of component B obtained in step S4 are mixed, and stirred at a temperature of 100-120° C. for 2-4 hours to obtain the high thermal conductivity potting glue.
[0011] Furthermore, step S1 is specifically as follows: by weight, 55 parts of modified bisphenol A epoxy resin, 2.5 parts of siloxane coupling agent, 5 parts of hollow glass microspheres and 1 part of zinc borate are mixed, and stirred at a temperature of 132° C. and a speed of 600 r / min for 50 minutes.
[0012] Furthermore, step S2 is specifically as follows: in parts by weight, 16 parts of polyether polyol, 3 parts of ethyl isocyanate acrylate and 0.65 parts of platinum catalyst are added to step S1, the temperature is increased to 170° C. at a rate of 5° C. / min, and the reaction is continued with stirring at a rate of 800 r / min for 2.5 hours to obtain component A.
[0013] Furthermore, step S3 is specifically as follows: in terms of weight, take 4 parts of spherical alumina, 6 parts of aluminum hydroxide, and 7 parts of silicon carbide, wherein the particle sizes of the three are 4 μm, 10 μm, and 20 μm, respectively; add 5 parts of graphene and 55 parts of ethanol solution, stir and react at a temperature of 95°C and a speed of 450 r / min for 68 minutes, and obtain a modified thermal conductive filler after filtering.
[0014] Furthermore, step S4 is specifically as follows: by weight, 45 parts of vinyl silicone oil, 10 parts of dimethyl silicone oil, 9 parts of modified thermal conductive filler, 14 parts of allyl glycidyl ether and 2 parts of silane coupling agent are mixed, and reacted at a temperature of 85° C. at a rate of 400 r / min for 42 minutes; the temperature is continued to be raised to 150° C. and stirred at a rate of 650 r / min for 60 minutes to obtain component B.
[0015] Furthermore, step S5 is specifically as follows: by weight, 45 parts of component A obtained in step S2 and 65 parts of component B obtained in step S4 are mixed, and the mixture is stirred at a temperature of 110° C. and a speed of 700 r / min for 2.5 hours to obtain the high thermal conductivity potting glue.
[0016] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. In the component A of the present invention, modified bisphenol A epoxy resin is used as a matrix, and a hydroxyl group in the polyether polyol and isocyanate ethyl acrylate isocyanate react chemically to form a polymer with high thermal conductivity; under the action of a siloxane coupling agent, hollow glass microspheres and zinc borate form a core-shell structure, which further increases the thermal conductivity and flame retardancy of the component A.
[0017] 2. In the component B of the present invention, vinyl silicone oil, dimethyl silicone oil, etc. are used as the matrix, and spherical alumina, aluminum hydroxide, silicon carbide mixture and graphene are used to prepare the thermal conductive filler. The spherical thermal conductive filler is used to improve the thermal conductivity of the colloid. Compared with irregularly shaped thermal conductive fillers, spherical thermal conductive fillers are easier to disperse; a network cross-linked state is formed by allyl glycidyl ether and a silane coupling agent, thereby improving the interface bonding strength.
[0018] 3. The present invention combines component A and component B to synergistically improve the thermal conductivity of the overall potting glue through two forms of thermal conductive systems, and has strong applicability and good application effect. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The modified bisphenol A epoxy resin used in the present invention is from Shandong Jiaying Chemical Technology Co., Ltd. with the item number EP-1307, the polyether polyol is from Jinjinle Chemical Co., Ltd. with the item number MN-700, the isocyanate ethyl acrylate is from Shanghai Yuanye Biotechnology Co., Ltd. with the item number S61233, the hollow glass microsphere is from Shanghai Saikerui Biotechnology Co., Ltd. with the item number SRCP-HGMS, the vinyl silicone oil is from Hubei Shiteng Chemical Technology Co., Ltd., the allyl glycidyl ether is from Wuhan Jiyesheng Chemical Co., Ltd. with the item number 4640, and the silane coupling agent is from Shandong Ruiqi Chemical Co., Ltd. with the item number 53.
[0021] Example 1 This embodiment provides a method for preparing a high thermal conductivity potting glue, comprising the following steps: S1: 40g of modified bisphenol A epoxy resin with an epoxy value of 0.42mol / 100g, 1g of siloxane coupling agent KH570, 4g of hollow glass microspheres and 0.5g of zinc borate were mixed, and stirred at a temperature of 120°C and a speed of 600r / min for 35min; S2: Add 12 g of polyether polyol, 2 g of ethyl isocyanate acrylate and 0.4 g of Karstedt catalyst to step S1, raise the temperature to 160° C. at a rate of 4° C. / min, continue stirring and reacting at a rate of 800 r / min for 1 h, and obtain component A; S3: Take 3g of spherical alumina, 4g of aluminum hydroxide, and 5g of silicon carbide, where the particle sizes of the three are 2μm, 8μm, and 18μm respectively; add 3g of graphene and 40g of ethanol solution, stir at a temperature of 80°C and a speed of 450r / min for 55min, and obtain a modified thermal conductive filler after filtering; S4: 30g vinyl silicone oil, 8g dimethyl silicone oil, 8g modified thermal conductive filler, 10g allyl glycidyl ether and 1g silane coupling agent were mixed, and reacted at a temperature of 75°C and a speed of 400r / min for 35min; the temperature was continued to rise to 140°C and stirred at a speed of 650r / min for 55min to obtain component B; S5: 30 g of component A obtained in step S2 and 40 g of component B obtained in step S4 were mixed, and the mixture was stirred at a temperature of 100° C. and a speed of 700 r / min for 2 h to obtain the high thermal conductivity potting adhesive.
[0022] Example 2 This embodiment provides a method for preparing a high thermal conductivity potting glue, comprising the following steps: S1: 60g of modified bisphenol A epoxy resin with an epoxy value of 0.47mol / 100g, 3g of siloxane coupling agent KH570, 7g of hollow glass microspheres and 1.5g of zinc borate were mixed, and stirred at a temperature of 140°C and a speed of 600r / min for 55min; S2: Add 20 g of polyether polyol, 4 g of ethyl isocyanate acrylate and 0.8 g of Karstedt catalyst to step S1, raise the temperature to 180° C. at a rate of 6° C. / min, continue stirring and reacting at a rate of 800 r / min for 3 h, and obtain component A; S3: Take 5g of spherical alumina, 8g of aluminum hydroxide, and 10g of silicon carbide, where the particle sizes of the three are 5μm, 12μm, and 22μm respectively; add 6g of graphene and 60g of ethanol solution, stir and react at a temperature of 100°C and a speed of 450r / min for 75min, and obtain a modified thermal conductive filler after filtering; S4: 50g vinyl silicone oil, 12g dimethyl silicone oil, 12g modified thermal conductive filler, 20g allyl glycidyl ether and 3g silane coupling agent were mixed, and reacted at a temperature of 95°C at a rate of 400r / min for 45min; the temperature was continued to rise to 160°C and stirred at a rate of 650r / min for 65min to obtain component B; S5: 60 g of component A obtained in step S2 and 70 g of component B obtained in step S4 were mixed, and stirred at a temperature of 120° C. and a speed of 700 r / min for 4 h to obtain the high thermal conductivity potting glue.
[0023] Example 3 This embodiment provides a method for preparing a high thermal conductivity potting glue, comprising the following steps: S1: 55g of modified bisphenol A epoxy resin with an epoxy value of 0.45mol / 100g, 2.5g of siloxane coupling agent KH570, 5g of hollow glass microspheres and 1g of zinc borate were mixed, and stirred at a temperature of 132°C and a speed of 600r / min for 50min; S2: Add 16 g of polyether polyol, 3 g of ethyl isocyanate acrylate and 0.65 g of Karstedt catalyst to step S1, raise the temperature to 170° C. at a rate of 5° C. / min, continue stirring and reacting at a rate of 800 r / min for 2.5 h, and obtain component A; S3: Take 4g of spherical alumina, 6g of aluminum hydroxide, and 7g of silicon carbide, where the particle sizes of the three are 4μm, 10μm, and 20μm respectively; add 5g of graphene and 55g of ethanol solution, stir and react at a temperature of 95°C and a speed of 450r / min for 68min, and filter to obtain a modified thermal conductive filler; S4: 45g of vinyl silicone oil, 10g of dimethyl silicone oil, 9g of modified thermal conductive filler, 14g of allyl glycidyl ether and 2g of silane coupling agent were mixed, and reacted at a temperature of 85°C at a rate of 400r / min for 42min; the temperature was further raised to 150°C and stirred at a rate of 650r / min for 60min to obtain component B; S5: 45 g of component A obtained in step S2 and 65 g of component B obtained in step S4 were mixed, and stirred at a temperature of 110° C. and a speed of 700 r / min for 2.5 h to obtain the high thermal conductive potting glue.
[0024] Comparative Example 1 The difference between this comparative example and Example 1 is that hollow glass microspheres and zinc borate are missing in step S1, and the other steps are the same.
[0025] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 is missing, and the other steps are the same.
[0026] Comparative Example 3 The difference between this comparative example and Example 1 is that graphene is missing in step S3, and the other steps are the same.
[0027] Comparative Example 4 The difference between this comparative example and Example 1 is that steps S1 and S2 are missing, and the other steps are the same.
[0028] Comparative Example 5 The difference between this comparative example and Example 1 is that steps S3 and S4 are missing, and the other steps are the same.
[0029] Comparative Example 6 The difference between this comparative example and Example 1 is that step S3 is missing, and the other steps are the same.
[0030] Performance Test: The test standard for thermal conductivity is ASTM-D5470, the test standard for tensile strength is GB / T528, and the flame retardant performance test adopts CB / T2409-84. The results are shown in the table below: Table 1 Performance test results
[0031] From the above performance test results, it can be seen that the thermal conductivity, tensile strength and flame retardancy of Examples 1-3 are good and effective, especially the comprehensive performance of Example 3 is the most outstanding.
[0032] However, the comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. The above experimental results further prove the importance of the technical solution defined in the present invention to its technical effect.
[0033] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high thermal conductivity potting glue, characterized in that: The invention is composed of 30-60 parts of component A and 40-70 parts of component B in parts by weight; wherein the component A comprises 40-60 parts of modified bisphenol A epoxy resin, 12-20 parts of polyether polyol, 2-4 parts of isocyanate ethyl acrylate, 1-3 parts of siloxane coupling agent, 0.4-0.8 parts of platinum catalyst, 4-7 parts of hollow glass microspheres and 0.5-1.5 parts of zinc borate; and the component B comprises 30-50 parts of vinyl silicone oil, 8-12 parts of dimethyl silicone oil, 8-12 parts of modified thermal conductive filler, 10-20 parts of allyl glycidyl ether and 1-3 parts of silane coupling agent.
2. A high thermal conductivity potting glue according to claim 1, characterized in that: The epoxy value of the modified bisphenol A epoxy resin is 0.42-0.47 mol / 100g.
3. The high thermal conductivity potting glue according to claim 1, characterized in that: The polyether polyol has a difunctional molecular weight of 2000; the siloxane coupling agent is KH570; and the platinum catalyst is a Karstedt catalyst.
4. The high thermal conductivity potting adhesive according to claim 1, characterized in that: The modified thermal conductive filler is a mixture of di-spherical aluminum oxide, aluminum hydroxide, silicon carbide and modified graphene, and the particle sizes are 2-5 μm, 8-12 μm, and 18-22 μm respectively.
5. A method for preparing a high thermal conductivity potting glue, characterized in that: The steps include: S1: by weight, 40-60 parts of modified bisphenol A epoxy resin, 1-3 parts of siloxane coupling agent, 4-7 parts of hollow glass microspheres and 0.5-1.5 parts of zinc borate are mixed, and stirred at a temperature of 120-140° C. for 35-55 minutes; S2: Add 12-20 parts of polyether polyol, 2-4 parts of ethyl isocyanate acrylate and 0.4-0.8 parts of platinum catalyst to step S1 by weight, increase the temperature to 160-180°C at a rate of 4-6°C / min, continue stirring and reacting for 1-3h to obtain component A; S3: Take 3-5 parts of spherical alumina, 4-8 parts of aluminum hydroxide, and 5-10 parts of silicon carbide by weight, wherein the particle sizes of the three are 2-5 μm, 8-12 μm, and 18-22 μm, respectively; add 3-6 parts of graphene and 40-60 parts of ethanol solution, stir and react at a temperature of 80-100°C for 55-75 minutes, and filter to obtain a modified thermal conductive filler; S4: Mix 30-50 parts of vinyl silicone oil, 8-12 parts of dimethyl silicone oil, 8-12 parts of modified thermal conductive filler, 10-20 parts of allyl glycidyl ether and 1-3 parts of silane coupling agent by weight, and react at a temperature of 75-95°C for 35-45 minutes; Continue to raise the temperature to 140-160°C and stir to react for 55-65 minutes to obtain component B; S5: By weight, 30-60 parts of component A obtained in step S2 and 40-70 parts of component B obtained in step S4 are mixed, and stirred at a temperature of 100-120° C. for 2-4 hours to obtain the high thermal conductivity potting glue.
6. The method for preparing a high thermal conductivity potting adhesive according to claim 5, characterized in that: Step S1 specifically comprises: mixing 55 parts of modified bisphenol A epoxy resin, 2.5 parts of siloxane coupling agent, 5 parts of hollow glass microspheres and 1 part of zinc borate by weight, and stirring at a temperature of 132° C. and a speed of 600 r / min for 50 minutes.
7. The method for preparing a high thermal conductivity potting adhesive according to claim 5, characterized in that: Step S2 is specifically as follows: by weight, 16 parts of polyether polyol, 3 parts of ethyl isocyanate acrylate and 0.65 parts of platinum catalyst are added to step S1, the temperature is raised to 170°C at a rate of 5°C / min, and the reaction is continued at a rate of 800r / min for 2.5h to obtain component A.
8. The method for preparing a high thermal conductivity potting adhesive according to claim 5, characterized in that: Step S3 is specifically as follows: in terms of weight, take 4 parts of spherical alumina, 6 parts of aluminum hydroxide, and 7 parts of silicon carbide, wherein the particle sizes of the three are 4 μm, 10 μm, and 20 μm, respectively; add 5 parts of graphene and 55 parts of ethanol solution, stir and react at a temperature of 95°C and a speed of 450 r / min for 68 minutes, and obtain the modified thermal conductive filler after filtering.
9. The method for preparing a high thermal conductivity potting compound according to claim 5, characterized in that: Step S4 is specifically as follows: by weight, 45 parts of vinyl silicone oil, 10 parts of dimethyl silicone oil, 9 parts of modified thermal conductive filler, 14 parts of allyl glycidyl ether and 2 parts of silane coupling agent are mixed, and reacted at a temperature of 85° C. and a speed of 400 r / min for 42 minutes; The temperature was continued to be raised to 150°C and stirred at a rate of 650 r / min for 60 min to obtain component B.
10. The method for preparing a high thermal conductivity potting adhesive according to claim 5, characterized in that: Step S5 is specifically as follows: by weight, 45 parts of component A obtained in step S2 and 65 parts of component B obtained in step S4 are mixed, and stirred at a temperature of 110° C. and a speed of 700 r / min for 2.5 hours to obtain the high thermal conductive potting glue.
Citation Information
Cited By
Efficient heat-conducting environment-friendly flame-retardant polyurethane foaming encapsulating material for battery module and preparation method of efficient heat-conducting environment-friendly flame-retardant polyurethane foaming encapsulating material
CN119930966A